2017
DOI: 10.1038/srep46156
|View full text |Cite
|
Sign up to set email alerts
|

Integrated host and viral transcriptome analyses reveal pathology and inflammatory response mechanisms to ALV-J injection in SPF chickens

Abstract: Avian leukosis virus (ALV) is detrimental to poultry health and causes substantial economic losses from mortality and decreased performance. Because tumorigenesis is a complex mechanism, the regulatory architecture of the immune system is likely to include the added dimensions of modulation by miRNAs and long-noncoding RNA (lncRNA). To characterize the response to ALV challenge, we developed a novel methodology that combines four datasets: mRNA expression and the associated regulatory factors of miRNA and lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…While in cattle the GC content were 48.79% and 51.38%, respectively ( Fig 3D). The present results that are in accordance with those of previous studies [33][34][35].…”
Section: A Boxplot Of Average Expression Level Histogram Of Lengthssupporting
confidence: 94%
“…While in cattle the GC content were 48.79% and 51.38%, respectively ( Fig 3D). The present results that are in accordance with those of previous studies [33][34][35].…”
Section: A Boxplot Of Average Expression Level Histogram Of Lengthssupporting
confidence: 94%
“…According to the RNA-seq technology, Lan combined four datasets: ALV gene expression, lncRNA, microRNA and mRNA to reveal pathology and inflammatory response mechanisms and the combined analysis revealed that the defenses gene family plays an important role in the immunosuppression caused by ALV-J [13]. The change of ALV-J injected DF-1 cells proteomic was detected by iTRAQ, and METAP2, PRDX1, ACTR3, ACTR5 may play vital roles in mechanism of ALV-J injection [14]. However, fewer studies have focused on the relationship of exosomes with ALV-J, what's more less the relationship between exosome proteins and RNA.…”
Section: Ivyspringmentioning
confidence: 99%
“…The shared significance and direction of effect between the analyses (NDV; heat + NDV), a lack of significance in the heat + NDV group, and a lack of significant haplotype by treatment interaction indicate the robustness of the action of IFI27L2 during viral challenge. Interferon alpha inducible protein 27 ( IFI27L2 ) has been previously shown to be upregulated in response to several viruses, including NDV [ 13 , 47 , 48 , 49 , 50 ]. The current study is the first record of association of IFI27L2 with antibody response and/or heat challenge.…”
Section: Resultsmentioning
confidence: 99%